A Phenomenological Study of Educators’ Experience After a Year of the COVID-19 Pandemic - Annamalai, Nagaletchimee; Ab Rashid, Radzuwan; Saed, Hadeel; Al-Smadi, Omar Ali; Yassin, Baderaddin (Frontiers in Psychology, 2022)
A phenomenological design was used in this study to investigate educators' lived experiences of teaching online in higher institutions in Malaysia. Data generation involved semi-structured interviews with 20 lecturers from three universities in the country. Data was analysed based on the thematic analysis approach and guided by the Technological, Pedagogical and Content Knowledge (TPACK)-self-efficacy framework. The findings revealed that after a year of teaching online, the potential of technology has been acknowledged by the educators after some trials and constraints were addressed. The domain related to TCK (Technology Content Knowledge), TPK (Technology Pedagogical Knowledge) TPACK were evident in the findings. However, Pedagogical Content Knowledge (PCK) was not given emphasis, hence the educators need to be constantly reminded of the significance of PCK (Pedagogical Content Knowledge). The emerging themes put forth in this paper can be a useful guide for educators when there is a need for them to teach online.